(untitled) (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2024)
Questioning skills are a fundamental aspect of learning that can enhance students’ cognitive engagement. Effective questions encourage students to think critically, analyze information, and build a more profound understanding. The questioning patterns of five pre-service science teachers during microteaching sessions were analyzed and categorized based on the four levels of cognitive engagement: Interactive, Constructive, Active, and Passive (ICAP) Theory. The findings indicate active questioning was the most dominant, while interactive, constructive, and passive questioning remained limited. The duration of interactive questioning was also relatively low, averaging only 6–8 minutes. In conclusion, pre-service teachers must still enhance their ques-tioning skills, particularly in developing constructive and interactive questions, to maximize students’ cognitive engagement in science learning.